ChemInform Abstract: Low‐Temperature Carbon—Chlorine Bond Activation by Bimetallic Gold/Palladium Alloy Nanoclusters: An Application to Ullmann Coupling. Issue 26 (6th June 2013) - Dhital, Raghu Nath; Kamonsatikul, Choavarit; Somsook, Ekasith; Bobuatong, Karan; Ehara, Masahiro; Karanjit, Sangita; Sakurai, Hidehiro
Abstract Bimetallic gold/palladium alloy nanoclusters are found to be efficient catalysts in the Ullmann coupling of chloroarenes in aqueous media at low temperatures.